Granular cell ameloblastoma of mandible - Trupti R. Jansari; Satarupa T. Samanta; Priti P. Trivedi; Manoj J. Shah (Wolters Kluwer Medknow Publications, 2014)
Ameloblastoma is a neoplasm of odontogenic epithelium, especially of enamel organ-type tissue that has not undergone differentiation to the point of hard tissue formation. Granular cell ameloblastoma is a rare condition, accounting for 3-5% of all ameloblastoma cases. A 30-year-old female patient presented with the chief complaint of swelling at the right lower jaw region since 1 year. Orthopantomogram and computed tomography scan was suggestive of primary bone tumor. Histopathologically, diagnosis of granular cell ameloblastoma of right mandible was made.